PENINGKATAN HASIL BELAJAR TAFSIR MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STAD PADA MAHASISWA FAKULTAS USHULUDDIN JURUSAN AQIDAH FILSAFAT IAIN PALU - Kamridah Kamridah (ISTIQRA, 2015)
This paper discusses the results of research on the implementation of cooperative learning model type STAD can improve learning outcomes interpretation courses through STAD cooperative learning methods in the students of the Faculty of Islamic Theology, Aqidah Philosophy Department IAIN Palu. This research is a class action (Classroom Action Research) are conducted in two cycles. The research was conducted at Faculty of Islamic Theology, the study population are students majoring in Aqidah Philosophy consisting of one class. Subjects numbered 38 people composed of 15 students and 23 female students. As for the sampling using random sampling techniques. The research was conducted in the fourth semester of the school year 2013/2014. The results showed that the application of cooperative learning model type STAD can improve learning outcomes interpretation courses through STAD cooperative learning methods on the student. This can be seen from the observation of the students and faculties are in very good category. And the results of tests in the first cycle is completed classes which gained 76,3% and for the second cycle obtained grade completed at 92.0%. Moderate to student learning motivation Aqidah Philosophy Department of Islamic Theology Faculty, after using STAD cooperative learning methods are more motivated in the learning process, both in terms of students working on worksheets and discussion are very active. It can be seen from the observation activities of students in the second cycle 1 meeting obtained by the percentage of the average value of 81.8% lecturer activity with very good categories and for the second meeting of the percentage obtained by the average value of student activities amounted to 90.9% by category very good